On diameters of some classes of analytical functions. II. - Vakarchuk , S. B. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
In the spaces Eq(Ω), q≥1, we consider the classes WrEp(Ω), p≥1, consisting of analytic functions f(z) ∈ EP(Ω) the integral moduli of continuity of whose r-th derivatives are majorized by a given nonnegative nondecreasing function Φ.